Proceedings of MOL2NET 2017, International Conference on Multidisciplinary Sciences, 3rd Edition 2017
DOI: 10.3390/mol2net-03-04609
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Quality indicators in <em>Ochroma pyramidale</em> seeds from three sites in the Ecuadorian Amazon for reforestation in degraded areas</strong>

Abstract: Ochroma pyramidale, is a species recognized for its economic and ecological importance, widely used in forest plantation programs. The aim of this work was to evaluate seed quality indicators of Ochroma pyramidale in three sites in the Amazon region of Ecuador for reforestation purpose in degraded areas. The results indicated that the seeds of the species in the three study sites are of good quality, expressed through the germinative capacity, germination energy, useful value and germinative vigor, although in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…The mechanisms regulating the start of germination are under selective pressures; thus, the variation of the germination capacity between and within the species is interpreted as an adaptation to the specific conditions of the local and regional habitat (Meyer et al, 1997). The reported percentages of GC for C. cateniformis are similar to the results obtained by Valencia et al, (2010), while for O. pyramidale the results are similar to what (García et al, 2017;Toledo-González et al, 2019), reported, and the results for S. macrophylla correspond to what and (Jácome-Segovia et al, 2019) described in their studies.…”
Section: Discussionsupporting
confidence: 88%
“…The mechanisms regulating the start of germination are under selective pressures; thus, the variation of the germination capacity between and within the species is interpreted as an adaptation to the specific conditions of the local and regional habitat (Meyer et al, 1997). The reported percentages of GC for C. cateniformis are similar to the results obtained by Valencia et al, (2010), while for O. pyramidale the results are similar to what (García et al, 2017;Toledo-González et al, 2019), reported, and the results for S. macrophylla correspond to what and (Jácome-Segovia et al, 2019) described in their studies.…”
Section: Discussionsupporting
confidence: 88%
“…Due to its advantageous rapid growth, pau de balsa stands out as a forest species that has a shorter response time when compared to other eucalyptus and teak species, and is therefore considered as a productive and profitable activity that can benefit small and medium producers (CRUZ et al, 2020;WEIRICH, 2008). The cultivation of pau de balsa for commercial purposes occupies large areas in Ecuador due to its diversity in use, making it the country with the highest production and trade of the species (GARCÍA et al, 2017). In Brazil, more specifically in Mato Grosso, the first plantations of pau de balsa were carried out speculatively, with materials from different sources and without the use of appropriate silvicultural practices, which resulted in planting areas with great variability in tree patterns in relation to the quality of the trunk and the density of the wood.…”
Section: Introductionmentioning
confidence: 99%